2010
DOI: 10.1002/chem.200902537
|View full text |Cite
|
Sign up to set email alerts
|

The Brønsted Acid Catalyzed, Enantioselective Vinylogous Mannich Reaction

Abstract: The first catalytic, enantioselective vinylogous Mannich reaction of acyclic silyl dienolates is reported. A second-generation 2,2'-dihydroxy-1,1'-binaphthyl (BINOL)-based phosphoric acid has been developed and further optimized as an enantioselective organocatalyst. Upon protonation of the imines, chiral contact ion pairs are generated in situ and attacked highly diastereoselectively by the nucleophile. gamma-Substituted silyl dienolates that lead to more highly substituted Mannich products with a second ster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 80 publications
0
37
0
4
Order By: Relevance
“…Subtle variations of the electronic and steric properties of these groups often have pronounced effects on the enantioselectivity. On the basis of computational studies [93] and crystal structures of hydrogen-bonded protioiminium•BINOL-derived phosphate ion pairs [9394] , it has been suggested that the importance of the 3,3′-substituents stems from their role in creating a specific substrate recognition site. In these systems, hydrogen-bonding interactions [95] with the bifunctional phosphoric acid moiety, as well as steric shielding [96] and stabilizing π-π interactions [97] with the 3,3′-substituents of the catalyst are proposed to provide the conformational constraints required for high stereoinduction.…”
Section: Chiral Anion-directed Catalysismentioning
confidence: 99%
“…Subtle variations of the electronic and steric properties of these groups often have pronounced effects on the enantioselectivity. On the basis of computational studies [93] and crystal structures of hydrogen-bonded protioiminium•BINOL-derived phosphate ion pairs [9394] , it has been suggested that the importance of the 3,3′-substituents stems from their role in creating a specific substrate recognition site. In these systems, hydrogen-bonding interactions [95] with the bifunctional phosphoric acid moiety, as well as steric shielding [96] and stabilizing π-π interactions [97] with the 3,3′-substituents of the catalyst are proposed to provide the conformational constraints required for high stereoinduction.…”
Section: Chiral Anion-directed Catalysismentioning
confidence: 99%
“…Auf der Grundlage von rechnerischen Untersuchungen [93] und Rçntgenstrukturen der über Wasserstoffbrücken gebundenen, von Protioiminium·BINOL abgeleiteten Phosphationenpaaren, [93,94] wurde angenommen, dass die Bedeutung der 3,3'-Substituenten von ihrer Rolle zur Erschaffung einer spezifischen Substraterkennungsstelle stammt. Eine häufig auftretende Gemeinsamkeit zwischen den meisten enantioselektiven Anionen dieser Art ist das Erfordernis sterisch anspruchsvoller 3,3'-Substituenten am BINOL-Gerüst.…”
Section: Nichtkovalente Wechselwirkungen Zwischen Kationischen Intermunclassified
“…Geringe Variationen der elektronischen und sterischen Eigenschaften dieser Gruppen haben oft deutliche Auswirkungen auf die Enantioselektivität. Auf der Grundlage von rechnerischen Untersuchungen [93] und Rçntgenstrukturen der über Wasserstoffbrücken gebundenen, von Protioiminium·BINOL abgeleiteten Phosphationenpaaren, [93,94] wurde angenommen, dass die Bedeutung der 3,3'-Substituenten von ihrer Rolle zur Erschaffung einer spezifischen Substraterkennungsstelle stammt. Es wurde vorgeschlagen, dass in diesen Systemen Wasserstoffbrücken [95] mit der difunktionellen Phosphorsäureeinheit ebenso wie die sterische Abschirmung [96] und stabilisierende p-p-Wechselwirkungen [97]…”
Section: Nichtkovalente Wechselwirkungen Zwischen Kationischen Intermunclassified
“…In general, the critical regiochemical issue can be addressed by judiciously preparing preformed, stable dienolate equivalents. This strategy has been successfully applied to asymmetric vinylogous aldol (17,21), Mannich (18,22), and Michael reactions (19,23). Avoiding the stoichiometric preactivation of the vinylogous nucleophilic components would logically improve this approach, particularly from the standpoint of atom economy (24).…”
Section: Microbiologymentioning
confidence: 99%